2014
DOI: 10.1017/s1751731114000123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk replacer and rumen inert fat on growth and reproduction of Malpura ram lambs

Abstract: The objective of this study was to assess the effects of milk replacer and rumen inert fat on growth, testicular development, puberty, semen production and sperm motion characteristics of ram lambs reared under intensive management in semi-arid climatic conditions. Seven-day-old male lambs of Malpura breed (n = 20) were divided equally into two groups. Up to weaning, the lambs in G1 group (control) were fed concentrate, green khejri (Prosopis cineraria) leaves and cowpea (Vigna unguiculata) hay along with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…In this study, lambs fed HF diet before day 60 had improved growth performance in terms of BW and ADG at both 60 and 120 days of age. Similarly, the study showed that the higher plane of nutrition in the form of milk replacer feeding during the preweaning period and rumen inert fat-supplemented feed during the post-weaning period to grow ram lambs enhances their growth (Kumar et al 2014). High energy feeding is required for the rapid growth of young lambs as high energy diets are used more efficiently in the growth promotion of young animals (Mahgoub et al 2000).…”
Section: Growth Performancementioning
confidence: 94%
“…In this study, lambs fed HF diet before day 60 had improved growth performance in terms of BW and ADG at both 60 and 120 days of age. Similarly, the study showed that the higher plane of nutrition in the form of milk replacer feeding during the preweaning period and rumen inert fat-supplemented feed during the post-weaning period to grow ram lambs enhances their growth (Kumar et al 2014). High energy feeding is required for the rapid growth of young lambs as high energy diets are used more efficiently in the growth promotion of young animals (Mahgoub et al 2000).…”
Section: Growth Performancementioning
confidence: 94%
“…In SCD the lambs are placed in adjacent pens for several weeks where they cannot suckle milk from the mother, but the social-affective contact between lamb and mother continues (Freitas-de-Melo and Ungerfeld, 2016). The study by Sowinska et al (2001) showed that temporary separation before weaning from 15 d of age improved the health and immune status of the lamb by supplementing with pre-and postweaning probiotics (Viérin and Bouissou, 2003;Kumar et al, 2014). It is unknown if SCD has a prolonged effect on stress levels or has a negative effect on post-weaning productive performance of lamb (Teixeira et al, 2014;Backes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%